Methods of competence assessment in vocational education and training (VET) in Germany - a systematic review : conducted on behalf of the Federal Ministry of Education and Research as part of the ASCOT+ Research and Transfer Initiative - Rüschoff, Britta [Verfasser] (Bundesinstitut für Berufsbildung, 2022)
"The present study provides a systematic overview of the methods of competence assessment in German vocational education and training (VET). To this end, 58 publications from the years 2001 to 2017 have been reviewed regarding the occupational areas for which assessment instruments were developed, types of competences that were assessed, the types of instruments used to assess the competences and the psychometric properties of these instruments. The results indicate that the instruments described in the reviewed publications particularly address commercial, industrial-technical and health occupations. The majority of the instruments deal with the identification of professional competences (66%), followed by basic (24%) and social/communicative competences (9%). Most instruments employed paper-and-pencil or computerized assessment methods with a clear trend towards computerized procedures. In most cases, the instruments were subjected to at least one type of validation. The reliabilities of the instruments varied greatly in some cases. In conclusion, this study shows that there is already a sound base of instruments available for the assessment of competence in German vocational education and training. However, the instruments should be extended to cover a broader range of occupational areas and subjected to additional validation and piloting prior to a potential large-scale transfer." (Editor, BIBB-Doku)
Keywords: L 6.2.1 Standards/Gütekriterien; S 6 Berufsbereiche; L 6.3.1 Diagnose- & Messinstrumente; 370; Kompetenz; Begriff; Definition; Berufsbildung; Kompetenzfeststellung; Kompetenzdiagnostik; Methode